2015
DOI: 10.1186/s40200-015-0205-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge and practice of community pharmacy personnel on diabetes mellitus management in Kathmandu district: a cross sectional descriptive study

Abstract: BackgroundPharmacists are the most reachable healthcare professionals to many chronically ill patients. It has been found that pharmacists see patients with diabetes up to five times more often than any other healthcare provider. Therefore, to provide quality health care to patients it is important that they have appropriate knowledge and practice on diabetes mellitus management. Thus, this study was conducted to assess the knowledge and practice of diabetes mellitus management among community pharmacy personn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 12 publications
(13 reference statements)
4
20
0
1
Order By: Relevance
“…The present study also showed that pharmacists during their education about insulin focused mainly on site and time of injecting insulin. This came in tune with similar finding reported in Nepal, where 51% of the pharmacists always educated the diabetic patients about the time of administration of their insulin 21 . Unfortunately, the current study showed that despite the involved pharmacists educate their patients about the time of using insulin, they failed to do so in appropriate manner, where most of them failed to specify the correct time for injecting regular insulin 30min before meal 15 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study also showed that pharmacists during their education about insulin focused mainly on site and time of injecting insulin. This came in tune with similar finding reported in Nepal, where 51% of the pharmacists always educated the diabetic patients about the time of administration of their insulin 21 . Unfortunately, the current study showed that despite the involved pharmacists educate their patients about the time of using insulin, they failed to do so in appropriate manner, where most of them failed to specify the correct time for injecting regular insulin 30min before meal 15 .…”
Section: Discussionsupporting
confidence: 89%
“…This malpractice of providing inadequate pharmaceutical care may be mainly attributed to the poor knowledge of the community pharmacists rather than lack of sufficient time, since the information provided by all pharmacists in all pharmacies without regard to number of patients and staff is poor. Similar finding was reported in Nepal, where only 1.9% of pharmacists reported to have good knowledge about diabetes and its treatment 21 .…”
Section: Discussionsupporting
confidence: 86%
“…Butt et al 2009). In one such study, it was made known that prolonged use of ARV drugs generally could increase the incidence of DM in these patients (Shrestha M et al 2015). The implication is that, patients should be selected in the choices of HAART regimen they would be treated with.…”
Section: Discussionmentioning
confidence: 99%
“…The good level was only observed at 13.16%. A lower proportion was found in Nepal [11]. A study conducted in Qatar had also shown a low to moderate level of knowledge among a large proportion of pharmacists [12].…”
Section: The Knowledgementioning
confidence: 95%